1998
DOI: 10.2105/ajph.88.3.467
|View full text |Cite
|
Sign up to set email alerts
|

Problem gamblers, problem substance users, and dual-problem individuals: an epidemiological study.

Abstract: OBJECTIVES: This study compared problem gamblers, problem substance users, dual-problem individuals, and persons without these problems in the general population. METHODS: On the basis of computer-assisted telephone interviews of a random sample of Texas adults (n = 6308) standard instruments were used to gauge substance use and gambling problems in the general population. RESULTS: Compared with those having a substance use or gambling problem only, dual-problem individuals were more likely to be young, never-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
3
12

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 11 publications
4
52
3
12
Order By: Relevance
“…Schissel (2001) suggested that youth may gamble in response to their feelings of disempowerment from society. Published research has associated various measures of socioeconomic status, including education (Cunningham-Williams et al, 1998), employment (Feigelman et al, 1998;Kearney, 2005b), and income (Kearney, 2005b) with problematic gambling. Individuals with lower socioeconomic status may consider gambling a form of investment (Weiss, 1988) and an escape from poverty (Schissel, 2001).…”
Section: Control Variables-mentioning
confidence: 99%
See 1 more Smart Citation
“…Schissel (2001) suggested that youth may gamble in response to their feelings of disempowerment from society. Published research has associated various measures of socioeconomic status, including education (Cunningham-Williams et al, 1998), employment (Feigelman et al, 1998;Kearney, 2005b), and income (Kearney, 2005b) with problematic gambling. Individuals with lower socioeconomic status may consider gambling a form of investment (Weiss, 1988) and an escape from poverty (Schissel, 2001).…”
Section: Control Variables-mentioning
confidence: 99%
“…The current analysis included dichotomous indicators for African American and other non-White races (White race was selected as the index category), a dummy variable for Hispanic or Latino ethnicity, along with an adjustment for birth outside the U.S. Published research suggests that non-married individuals are more likely to gamble (Feigelman et al, 1998 ;Kearney, 2005b). Those who choose not to marry or to leave a marriage may face less responsibility and therefore have more opportunity to gamble relative to married individuals who must also consider the needs of their spouses and/or children.…”
Section: Control Variables-mentioning
confidence: 99%
“…In fact, gamblers who also have another form of dependence (e.g. alcohol or drugs) present a more severe clinical picture when entering treatment and report more mental health problems when compared with those who have one dependence problem (Arseneault et al 2001;Cunningham-Williams et al 2000;Feigelman et al 1998;Fernandez-Montalvo et al 2012;Hall et al 2000;Liu et al 2009;Mathias et al 2009;Petry 2007). Treatment studies concerning cocaine users have found those with gambling problems to be more likely unemployed, to have had a higher prevalence of antisocial personality disorders and more frequent issues with the justice system (Hall et al 2000;Toneatto and Brennan 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Les évaluations des deux groupes présentent un indice de gravité minimal de 4 sur 9 sur leurs habitudes de JHA, soit le seuil requis pour recevoir une intervention en JHA dans les CRD du Québec. Puisque la concomitance d'abus/dépen-dance aux substances psychoactives (SPA) chez les JP est associée à une aggravation des difficultés personnelles, interpersonnelles, professionnelles et judiciaires (Bronnec et al, 2010 ;Feigelman et al, 1998 ;Ladd et Petry, 2003 ;Pietrzak et al, 2005) L'évaluation faite à partir de l'IGT prend la forme d'une entrevue semi-structurée d'environ deux heures trente et dresse un portrait exhaustif de la situation de la personne selon sept sphères : Alcool, Drogues, Relations familiales/interpersonnelles, État psychologique, Emploi/ressources, Situation judiciaire et État de santé physique. Les questions de l'IGT portent à la fois sur l'ensemble de la vie et sur les 30 jours précédant l'évaluation.…”
Section: Critères De Sélection Et D'exclusionunclassified